2015
DOI: 10.1016/j.kjms.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

EphA2 modulates radiosensitive of hepatocellular carcinoma cells via p38/mitogen‐activated protein kinase‐mediated signal pathways

Abstract: This experiment was conducted to investigate the role of EPH receptor A2 (EphA2) in the modulation of radiosensitivity of hepatic cellular cancer (HCC) cells and to determine whether p38/mitogen-activated protein kinase (p38MAPK) signaling mediated EphA2 function in this respect. The protein expressions of EphA2 and phosphorylated p38MAPK were tested in HCC and normal hepatic tissues. In HCC 97H cells, EphA2 was overexpressed and knocked out by transfection with EphA2 expression vector and EphA2-ShRNA, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Notably, HBx has been reported to be the activator of the Src family of tyrosine kinases, which could activate the Ras‐Raf‐MAPK pathway to affect the proliferation and apoptosis of HBV‐related HCC, and at the same time, the activation of Src also enhanced the activity of viral polymerase and thereby promoting HBV replication . As we know, ERK/12 and p38MAPK are two of the most important pathways in MAPK signalling, and a previous study confirmed that EphA2 can regulate p38MAPK and ERK1/2 signalling pathway to affect cell growth . Therefore, we determined the proliferation and apoptosis of HepG2.2.15 and pHBV1.2+ Huh7 cell, as well as the expressions of pathway‐related proteins, and found that upregulation of miR‐520e inhibited cell proliferation and blocked p38MAPK and ERK1/2 pathways, whereas inhibiting miR‐520e led to completely opposite results, and si‐EphA2 reversed the effect of miR‐520e inhibitor.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Notably, HBx has been reported to be the activator of the Src family of tyrosine kinases, which could activate the Ras‐Raf‐MAPK pathway to affect the proliferation and apoptosis of HBV‐related HCC, and at the same time, the activation of Src also enhanced the activity of viral polymerase and thereby promoting HBV replication . As we know, ERK/12 and p38MAPK are two of the most important pathways in MAPK signalling, and a previous study confirmed that EphA2 can regulate p38MAPK and ERK1/2 signalling pathway to affect cell growth . Therefore, we determined the proliferation and apoptosis of HepG2.2.15 and pHBV1.2+ Huh7 cell, as well as the expressions of pathway‐related proteins, and found that upregulation of miR‐520e inhibited cell proliferation and blocked p38MAPK and ERK1/2 pathways, whereas inhibiting miR‐520e led to completely opposite results, and si‐EphA2 reversed the effect of miR‐520e inhibitor.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, using the target gene prediction website, we found that EphA2 was the target gene of miR‐520e, and it could regulate the MAPK signalling pathway in HCC cells, as indicated by Jin et al . More importantly, HBx has been demonstrated to participate in the development and progression of HBV‐related HCC by activating the MAPK signalling pathway .…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Wound healing assays may be used to detect cellular self-repairing capability following wound. A lower cell migration rate indicates slower proliferation and weaker self-repairing capability, which in turn suggests a higher radiosensitivity (32). Furthermore, previous studies have reported that upregulated cyclin D1 was associated a high incidence of cervical lymph node metastasis of squamous cell carcinoma (33).…”
mentioning
confidence: 99%